Host Range Determinants of Pseudomonas savastanoi Pathovars of Woody Hosts Revealed by Comparative Genomics and Cross-Pathogenicity Tests - Moreno-Pérez, Alba; Pintado, Adrián; Murillo, Jesús; Caballo-Ponce, Eloy; Tegli, Stefania; Moretti, Chiaraluce; Rodríguez-Palenzuela, Pablo; Ramos, Cayo (Frontiers in Plant Science, 2020)
The study of host range determinants within the Pseudomonas syringae complex is gaining renewed attention due to its widespread distribution in non-agricultural environments, evidence of large variability in intra-pathovar host range, and the emergence of new epidemic diseases. This requires the establishment of appropriate model pathosystems facilitating integration of phenotypic, genomic and evolutionary data. Pseudomonas savastanoi pv. savastanoi is a model pathogen of the olive tree, and here we report a closed genome of strain NCPPB 3335, plus draft genome sequences of three strains isolated from oleander (pv. nerii), ash (pv. fraxini) and broom plants (pv. retacarpa). We then conducted a comparative genomic analysis of these four new genomes plus 16 publicly available genomes, representing 20 strains of these four P. savastanoi pathovars of woody hosts. Despite overlapping host ranges, cross-pathogenicity tests using four plant hosts clearly separated these pathovars and lead to pathovar reassignment of two strains. Critically, these functional assays were pivotal to reconcile phylogeny with host range and to define pathovar-specific genes repertoires. We report a pan-genome of 7,953 ortholog gene families and a total of 45 type III secretion system effector genes, including 24 core genes, four genes exclusive of pv. retacarpa and several genes encoding pathovar-specific truncations. Noticeably, the four pathovars corresponded with well-defined genetic lineages, with core genome phylogeny and hierarchical clustering of effector genes closely correlating with pathogenic specialization. Knot-inducing pathovars encode genes absent in the canker-inducing pv. fraxini, such as those related to indole acetic acid, cytokinins, rhizobitoxine, and a bacteriophytochrome. Other pathovar-exclusive genes encode type I, type II, type IV and type VI secretion system proteins, the phytotoxine phevamine A, a siderophore, c-di-GMP-related proteins, methyl chemotaxis proteins and a broad collection of transcriptional regulators and transporters of eight different superfamilies. Our combination of pathogenicity analyses and genomics tools allowed us to correctly assign strains to pathovars and to propose a repertoire of host range-related genes in the P. syringae complex.